MiR‐129 targets CDK1 and iASPP to modulate Burkitt lymphoma cell proliferation in a TAp63‐dependent manner. Issue 11 (13th August 2018) - Zou, Hui; Zou, Runying; Chen, Keke; Zhu, Chengguang; Tian, Xin; You, Yalan; He, Xiangling
Abstract: Burkitt lymphoma is one of the most common lymphatic system cancers with poor outcome in adult patients. p53‐induced apoptosis is a critical signaling for preventing tumor development. Cyclin B/cyclin‐dependent kinase 1 (CDK1) phosphorylates inhibitor of apoptosis stimulating protein of P53 (iASPP) to promote iASPP nucleus localization and its inhibitory effect on p53. However, p53 is frequently mutated in Burkitt lymphoma, which gains novel oncogenic properties. Recently, the p53 family member, p63, became an attractive gene for the therapeutic strategies for patients with cancer. Therefore, we investigated the role of iASPP in the transactivation domain p63 (TAp63)‐dependent cell proliferation inhibition in Burkitt lymphoma. We verified that the oncogenic effect of iASPP on Burkitt lymphoma is TAp63 dependent rather than p53 and confirmed that the interaction between CDK1 and iASPP enhanced the inhibitory effect of iASPP on p53 and TAp63. An online tool predicated that miR‐129 might bind to 3′‐untranslated region of iASPP and CDK1. We revealed that miR‐129 acted as a tumor suppressor by inhibiting cancer cell proliferation and inhibiting CDK1 and iASPP via direct binding. An miR‐129 inhibitor increased nucleus iASPP and decreased nucleus p53 and TAp63 levels, which could be reversed by the CDK1 knockdown, indicating that miR‐129 might target CDK1 to inhibit iASPP phosphorylation, thus hindering iASPP nucleus localization and its inhibitory effect on p53 and TAp63 protein levels. Taken together, miR‐129 could targetedly inhibit the expression of CDK1 and iASPP. CDK1 knockdown inhibits iASPP S84/S113 phosphorylation, thus blocking iASPP nucleus localization, suppressing the inhibitory effect of iASPP on p53 and TAp63, and restoring TAp63‐induced proliferation inhibition in Burkitt lymphoma cells. Abstract : miR‐129 acts as a tumor suppressor in Burkitt lymphoma through targeting cyclin‐dependent kinase 1 and iASPP to restore TAp63‐mediated cancer cell proliferation; miR‐129 presents a novel target of Burkitt lymphoma treatment.